2019
DOI: 10.1002/jgc4.1115
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between genetic counseling student self‐efficacy and clinical training

Abstract: Clinical experience is an important part of the training required in genetic counseling graduate programs, but little evidence exists for the number of clinical cases a student may need in order to confidently perform skills. The purpose of this study was to further describe the relationship between genetic counseling student self‐efficacy and the number of core cases students log during their training. In this study, second year genetic counseling students nearing the end of their training completed a questio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
7
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 18 publications
3
7
2
Order By: Relevance
“…In the current study, the highest mean self‐efficacy was for information gathering (96.2 ± 6.1) and the lowest mean self‐efficacy was for complex skills (86.9 ± 11.1). This phenomenon was also observed in Caldwell et al () study and Owens‐Thomas et al () study. The mean GCSES factor scores in the current study were higher for all six factors than those reported in genetic counseling students at the beginning of their second year of training (Caldwell et al, ) and at the end of their second year of training (Owens‐Thomas et al, ) (Table ).…”
Section: Resultssupporting
confidence: 79%
See 3 more Smart Citations
“…In the current study, the highest mean self‐efficacy was for information gathering (96.2 ± 6.1) and the lowest mean self‐efficacy was for complex skills (86.9 ± 11.1). This phenomenon was also observed in Caldwell et al () study and Owens‐Thomas et al () study. The mean GCSES factor scores in the current study were higher for all six factors than those reported in genetic counseling students at the beginning of their second year of training (Caldwell et al, ) and at the end of their second year of training (Owens‐Thomas et al, ) (Table ).…”
Section: Resultssupporting
confidence: 79%
“…A further aim was to look at professional experiences and job characteristics of genetic counselors in relation to self‐efficacy with genetic counseling skills. Lastly, the current study aimed to provide further validation of the GCSES by confirming the six‐factor model that has been demonstrated in previous studies (Caldwell et al, ; Owens‐Thomas et al, ). Self‐efficacy is an important factor, separate from competence, which can impact individual performance during training and on the job.…”
Section: Introductionsupporting
confidence: 77%
See 2 more Smart Citations
“…This can help the novice supervisor feel more comfortable and confident with few students supervised (Allsbrook et al, ). The competencies can be used by supervisors as a guide for their rotations. For example: Conduct an orientation with a contract regarding the details of the clinical placement and supervisory relationship, as well as set realistic learning goals with student and comment on positive changes made by students in response to feedback (Eubanks Higgins et al, ). Supervisors can create an informed consent to review with students to orient them to the rotation, expectations, how to handle boundary issues (e.g., more than one relationship present between student and supervisor; Gu et al, ; Hendrickson et al, ; McCarthy & LeRoy, ). It may be that some students are seeing more patients than are necessary per rotation (Owens‐Thomas, Wusik, He, Yager, & Atzinger, ). Setting shorter rotations or giving more breaks to supervisors may also be a way to reduce GC supervisor burden (Berg et al, ). Program directors could potentially increase supervisors by utilizing genetic counselors farther away from a training program during summer rotations.…”
Section: Discussionmentioning
confidence: 99%